Development of a Collaborative Community Service Program Based on Literacy, Writing Therapy, and SRQ Screening as a Preventive Strategy For Students' Mental Health Syafira - Syafira Putri Ramadhani (Universitas Islam Balitar, 2026)
This Community Service activity aims to strengthen literacy education through mental health screening using the Self-Reporting Questionnaire (SRQ) and the application of writing therapy as a means of expressive literacy. Thirty-two students participated in this activity. The SRQ screening results indicated that most students fell into the low category for indications of psychological disorders, while others fell into the moderate and high categories. These findings formed the basis for implementing writing therapy, which aimed to improve writing skills and help participants express their thoughts and feelings in writing. The evaluation of the activity showed a very positive response, with the majority of participants stating that they understood the material, were able to participate effectively in the activities, and felt a positive impact on themselves. Therefore, this This Community Service activity can be concluded as an effective effort to strengthen literacy education integrated with a psychosocial support approach for students.